On South Bank : the production of public space - Jones, Alasdair (Re-materialising cultural geography., 2014)
Through an in-depth ethnographic examination of London's 'South Bank', this book explores the value widely presupposed on urban public space. Based on subjective accounts of the value of public space, as well as observations of how the South Bank is used and 'practised' on a daily basis, it argues that this value is not so much inherent to physical public space itself as it is derived through the everyday use and production of that space. Public space is valued not only for its essential material characteristics but also for the productive potential that these characteristics, if properly mana.